Applying (ACTFL) Standards to Arabic Language Education and the Challenges of Artificial Intelligence An Analytical Study - Abdallah, Abdallah Saleh; Al-Haddad, Abdulwahab Abdulaziz Kassem; Talib, Noor Husna; Ibrahim Youssef, Mohamed Abdelrahman; Zolmaily, Muhammad Akmal (Penerbit UniSIRAJ UNIVERSITI ISLAM ANTARABANGSA TUANKU SYED SIRAJUDDIN, 2025)
This analytical study explores the application of the American Council on the Teaching of Foreign Languages (ACTFL) standards in Arabic language education, focusing particularly on the emerging challenges and opportunities posed by artificial intelligence (AI). As AI technologies continue to reshape the landscape of language instruction globally, integrating ACTFL standards -which emphasize linguistic proficiency, intercultural competence, and communicative effectiveness- into Arabic teaching environments presents both pedagogical potential and significant complexity. Arabic is a linguistically rich language with morphological diversity, syntactic complexities, and regional dialectal variations that hinders the effectiveness of generalized AI language tools. The core problem addressed in this study is the limited understanding of how AI-powered educational tools align with ACTFL standards in the context of Arabic language instruction, particularly concerning cultural authenticity, grammar accuracy, and assessment validity. To investigate this, the study employed a content analysis approach using the Scopus Analyzer tool. Results indicate a growing body of literature that connects AI innovations with second language instruction, yet a noticeable gap remains in addressing Arabic specifically. Only some of the analyzed papers explicitly focused on Arabic education, and even fewer engaged with ACTFL-aligned frameworks. While AI has shown promise in areas such as personalized learning, grammar feedback, and pronunciation support, it struggles with capturing dialectal nuance and cultural subtleties central to ACTFL’s five Cs (Communication, Cultures, Connections, Comparisons, and Communities). The study concludes that for AI tools to be effectively deployed in Arabic language education, they must be tailored to the linguistic and cultural realities of Arabic-speaking learners. Furthermore, alignment with ACTFL standards should not only guide instructional content but also inform the development of AI algorithms and feedback systems. These findings offer a foundation for future curriculum development, policy formulation, and interdisciplinary collaboration between educators and AI developers aiming to uphold international language education standards in a culturally authentic manner.